The Influence Of Principal Leadership On School Culture And Teacher Performance: A Literature Review - Mansur Sihadji (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the relationship between principal leadership, school culture, and teacher performance from the perspective of educational management and social sciences through a Systematic Literature Review (SLR) approach. The research employed a descriptive qualitative method using the PRISMA framework to ensure a systematic and comprehensive review process. Data were collected from scientific publications published between 2015–2025 through databases including Google Scholar, Scopus, SINTA, ERIC, and DOAJ. Data analysis used content analysis to identify themes, research trends, and relationships among variables. The findings indicate that principal leadership significantly influences school culture and teacher performance. Transformational, democratic, and visionary leadership models are effective in improving teacher motivation, organizational commitment, collaboration, and learning quality. Positive school culture also contributes to student character development, discipline, innovation, and sustainable educational improvement. Furthermore, digital transformation and globalization require school leaders to possess adaptive and innovative leadership skills. This study contributes to the development of educational management theory and provides practical references for strengthening school leadership and organizational culture.